Innate Immune Recognition and Inflammasome Activation in Listeria Monocytogenes Infection - Eitel, Julia; Suttorp, Norbert; Opitz, Bastian (Frontiers in Microbiology, 2011)
Listeria monocytogenes is an intracellular, Gram-positive bacterium that can cause life-threatening illness especially in immunocompromised individuals and newborns. The pathogen propagates within the cytosol of various host cells after escaping from the phagosomal compartment depending on the cytolysin listeriolysin O. While L. monocytogenes can manipulate the endocytic and many host cell signalling cascades to its advantage, host cells are however capable of detecting Listeria infection at different cellular compartments by expressing innate immune receptors that trigger antibacterial defense pathways. These receptors include the Toll-like receptors (TLRs), NOD-like receptors (NLRs), and cytosolic DNA sensors. Some NLRs as well as the DNA sensor AIM2 form multiprotein complexes called inflammasomes. Inflammasomes regulate caspase-1-dependent production of the key inflammatory cytokines IL-1beta and IL-18 as well as pyroptotic cell death in L. monocytogenes-infected cells. This review describes the current knowledge about innate immune sensing and inflammasome activation in Listeria infection.